RHEUMATOID LUNG DISEASE AS A PRESENTING FEATURE OF RHEUMATOID ARTHRITIS (Case Report) - Pınar Borman,; Gülseren Ak,; Serap Yücel Gökçek,; Arzu Ertürk,; Selçuk Coşkun,; Hatice Bodur,; Funda Demirağ, (Archives of Rheumatology, 2002)
Pulmonary involvement is a common extraarticular feature of rheumatoid arthritis (RA) but early symptomatic manifestations of (RA) are uncommon. We present 2 male RA patients with all characteristics features of pulmonary involvement which preceded the articular symptoms and occured concurrently. Case 1; A 32-year-old male presented with severe pulmonary involvement due to the rheumatoid nodules, pleurisy, atalectasis, interstitial fibrosis which preceded the articular symptoms. Case 2; A 54-yearold male presented with articular manifestations of RA associated with typical pulmonary findings of rheumatoid lung including paranchimal nodules, pleurisy, interstitial fibrosis and honey-comb appearance simultaneously. In both cases the diagnosis were made after exclusion of other causes of pulmonary disease and depending on the findings of pleural biopsy. Both cases were notable for having all the characteristic features of rheumatoid lung as an early manifestation of RA. In conclusion severe typical pulmonary findings may be the initial symptoms and physicians must be aware of this extraarticular finding as a presenting feature of RA.